Clinical Neuropathology Practice News 4-2012: levels of evidence for brain tumor biomarkers - Berghoff, Anna Sophie (Dustri-Verlag Dr. Karl Feistle, 2012)
The National Comprehensive Cancer Network (NCCN) recently published a task force report on the evaluation of the clinical utility of tumor biomarkers in oncology. In this report, common terminology and the use of levels of evidence scores to aid the evaluation of biomarker tests in oncology were proposed. Furthermore, the task force applied a level of evidence system to selected biomarkers of several cancer types. According to this system, the highest level of evidence, IA, is granted to a biomarker only if it has been evaluated in at least one adequately powered and specifically designed prospective controlled trial. For gliomas, only 1p/19q testing in oligodendroglial tumors was classified as IA by the NCCN task force. For all of the following biomarkers the present evidence level for clinical utility was regarded as lower than that of 1p/19q status: MGMT gene promoter methylation testing (glioblastoma), IDH mutation testing (diffusely growing gliomas), BRAF fusion testing (pilocytic astrocytoma) and CIMP testing (diffusely growing gliomas). The task force acknowledged that the exact application of levels of evidence needs further refinement. To our mind, the implementation of a brain tumor expert panel seems vital to evaluate the evidence levels of neurooncological biomarkers according to generally accepted criteria on a regular basis. Systematic identification of current research needs and widely accepted up-to-date recommendations for efficient biomarker application in everyday practice could be gained.